Schiphol S, Amsterdam (Holanda) - Koolhaas, Rem (2001)
Traslado del aeropuerto de Schiphol a una isla artificial en el mar del Norte
Keywords: PAISES BAJOS; AMSTERDAM; OMA; AEROPUERTOS; URBANIZACIONES; UTOPIAS